Effectiveness of Citronella and Patchouli Waste as Oyster Mushroom Substrates - Diah Ayu Pramudha Wardhani; Elis Herliyana; Irdika Mansur (Jurnal Ilmu Pertanian Indonesia, 2026)
The essential oil industry produces large amounts of underutilized solid waste containing lignocellulosic compounds that can potentially support the growth of edible mushrooms. This research was conducted to evaluate the potential utilization of solid waste from citronella (Cymbopogon nardus (L.) Rendle) and patchouli (Pogostemon cablin (Blanco) Benth.) as alternative substrates for oyster mushroom (Pleurotus spp.) cultivation. The experimental design employed a completely randomized factorial design incorporating two treatment factors: oyster mushroom varieties (white and brown strains) and eight substrate composition variations, with one control treatment serving as a baseline comparison. Substrate formulations were developed using various combinations of citronella and patchouli waste mixed with conventional materials. The results demonstrated that aromatic waste-based substrates with balanced formulations, specifically M1, M2, and M5, produced significantly higher fresh weights and fruiting body counts, closely approaching the performance of the control treatment (M0B1), which recorded the highest biological efficiency of 42.37% within a cultivation period of approximately 56 days. Conversely, single dominant waste substrates, such as M3 and M6, yielded smaller fruiting bodies and lower total biomass production. Statistical analysis revealed a positive correlation between fruiting body quantity and fresh weight, supporting the use of morphological traits as reliable indicators of cultivation productivity. These findings highlight the significant potential of essential oil industry waste as a sustainable and economically viable alternative cultivation medium for oyster mushroom production, provided that substrates are formulated with appropriate proportional compositions and are properly adapted to their specific chemical characteristics and nutritional properties. Keywords: biological efficiency, citronella, growth media, patchouli, Pleurotus spp.